2013
DOI: 10.1002/ijc.28327
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively spliced tissue factor contributes to tumor spread and activation of coagulation in pancreatic ductal adenocarcinoma

Abstract: Alternatively spliced tissue factor (asTF) promotes neovascularization and monocyte recruitment via integrin ligation. While asTF mRNA has been detected in some pancreatic ductal adenocarcinoma (PDAC) cell lines and increased asTF expression can promote PDAC growth in a subcutaneous model, the expression of asTF protein in bona fide PDAC lesions and/or its role in metastatic spread are yet to be ascertained. We here report that asTF protein is abundant in lesional and stromal compartments of the five studied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
94
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(98 citation statements)
references
References 32 publications
4
94
0
Order By: Relevance
“…In 2011, we found that increased amounts of asTF in cell culture media induced migration of THP-1 leukemia cells in vitro (10 ). In line with this, Unruh et al showed that increased asTF expression in pancreatic ductal adenocarcinomas led to the generation of metastases in distal lymph nodes of mice (25 ). In human endothelial cells, van den Berg and colleagues demonstrated that asTFinduced cell migration is mediated via integrin ␣v␤3 interaction (24 ).…”
Section: The Role Of Tf Isoforms In Cancer Cell Migration Tumor Metamentioning
confidence: 72%
See 4 more Smart Citations
“…In 2011, we found that increased amounts of asTF in cell culture media induced migration of THP-1 leukemia cells in vitro (10 ). In line with this, Unruh et al showed that increased asTF expression in pancreatic ductal adenocarcinomas led to the generation of metastases in distal lymph nodes of mice (25 ). In human endothelial cells, van den Berg and colleagues demonstrated that asTFinduced cell migration is mediated via integrin ␣v␤3 interaction (24 ).…”
Section: The Role Of Tf Isoforms In Cancer Cell Migration Tumor Metamentioning
confidence: 72%
“…In both studies, the low procoagulant potential of asTF was dependent on its association with phospholipid surfaces in vitro and in vivo (25,26 ). These findings indicate that, if at all, asTF exhibits only low prothrombogenic potential (7,25 ). Thus, the influence of asTF on cancerrelated thrombosis remains unclear.…”
Section: The Role Of Tf Isoforms In Cancer-related Thrombosismentioning
confidence: 86%
See 3 more Smart Citations